The Use of Short Comics and its Impact on Students’Writing Skill - Provesa, Aflakha Hakim (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2014)
The purpose of the study was to determine the effectiveness of using short comics in teaching of narrative writing at one Islamic Junior High School in Kediri, Indonesia. By conducting an experimental study, the subjects of the study were divided into two groups, group 1: using short comics, and group 2: conventional method. For analyzing the data, t-test was utilized by using students’ writing score in all elements namely content, organization, vocabulary, languange use, and mechanics. The findings indicated that there is a significant difference on the students’ writing score between the control and the experimental groups. The value of t-obtained (2.38) is greater than t-table (2.0639) with the degree of freedom (df) 24 at 5% significance level. It means there is a significant effect of using short comics in teaching writing.